Um espectro ronda as pequenas cidades : o aumento da violência e da insegurança objetiva - Fernandes, Pedro Henrique Carnevalli (2017)
Once upon a time, there was a small, quiet and safe town where doors and windows were always opened... this represents a simple sentence that synthesizes the theses. The wish for the comprehension of the contradictions in human and social life condition tied to production processes of urban space and transience in the dynamics of the small towns are the main motivation for the subsidies and contributions of this research. The dialectic freedom-security proposed in the thesis is essentially understood as the condition that separates freedom from security when they should, perhaps idealistically, connect them to happen simultaneously. So, in the name of security, doors and windows are getting closed in small towns! However, people are also getting closed for sociability, space and public life. The main purpose of this thesis is to analyze and understand the processes and explanations for the existence of violence and insecurity in small towns and its implications in urban spaces and in the local society daily life since different spatial dimensions of analysis (global, national, regional and local). There are three concomitant reasons that explains this: the dissemination and the overflow of the metropolitan sociability, specially by media and internet; the illicit trafficking spread without boarders and barriers, which articulates to networked economy and influences small towns similarly to globalization; and the loss of centrality and the demographic emptying of urban centers that cooled down many services, including public security. The methodological procedures were systematized and organized in six stages: bibliographic survey, demographic and social indicators survey of the cities from Northern Paraná, selection of the small cities for a local stage analysis, additional survey to understand the explanatory reasons, conduction of fieldwork (questionnaires and interviews and photographic register), systematization of information and data collected and preparation of maps and final draft. The results revealed that regardless to the explanation for the occurrence, there is a huge concern about violence and insecurity and different strategies of sociability and resistance. Thus, alarming and frequent situations were found, as the violence generated by the society and the one played by the State, the spread of the drug trafficking from international, regional and even local groups and the weakness of life condition. It must be thought from human empowerment by the real feeling of freedom and, at the same time, close to an effective public security.